THE ROLE OF NUTRITION IN PERSONS WITH DISABILITIES - Belovičová, M.; Popovičová, M. (Україна. Здоров’я нації, 2023)
Disability is often seen as a specialist subject and therefore not mainstreamed into education for practitioners in nutrition, health and child development. Pre- and in-service training of professionals in health-care, nutrition and development on the links between disability and nutrition would increase awareness of the specific nutrition requirements of children with disabilities, and expand more inclusive programmes and practice. As nutrition efforts are scaled up, the needs of children and adults with disabilities must be integrated to ensure that they are offered the same life-saving interventions as other children. Nutrition interventions for all children and adults will also benefit children and adults with disabilities. In order to ensure effective and inclusive nutrition, special attention should be paid by nutritionists, health-care and community service-providers to include children at high risk of becoming malnourished (such as those with existing disability or chronic disease) in existing nutrition programmes, as well as adapting or expanding community-based models of care and reaching out to institutions in which some children and adults with disabilities live. Adults with developmental disabilities and children and youth with special health care needs have multiple risk factors requiring nutrition interventions, including growth alterations (eg, failure to thrive, obesity, or growth retardation), metabolic disorders, poor feeding skills, drug-nutrient interactions, and sometimes partial or total dependence on enteral or parenteral nutrition. Comorbid conditions such as obesity or endocrine disorders that require nutrition interventions are also more likely to develop as the population ages. Poor nutrition-related health habits, limited access to services, and long-term polypharmacy are considered significant health risk factors and registered nutrition dietetics technicians are vital in providing comprehensive care to these individuals. The international community – governments, policy-makers, multi- and bilateral donors and practitioners – must ensure political and resource commitment to tackling nutrition and disability as related issues. For some children with disabilities as well as for adults with disabilities, there is also a need for disability-specific services which target and address their needs and those of their families or caretakers, including professional special and community-based rehabilitation services where these are available.